1995
DOI: 10.1007/bf02252363
|View full text |Cite
|
Sign up to set email alerts
|

An empirical couple typology based on differentiation

Abstract: ABSTRACT. Both spouses of 100 married, heterosexual couples completed the Personal Authority in the Family System Questionnaire (PAFS-Q). A cluster analysis of the couples' scores on the four intimacy and fusion scales of the PAFS-Q produced four clusters that were meaningfully distinct in the patterns of differentiation of the wives and husbands. Couples comprising these clusters are described in terms of intergenerational theories of family interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…This strategy has been used in other studies employing similar clustering techniques (see Fowers & Olson, 1992; Lavee & Olson, 1993). Following a procedure outlined by Bayer and Day (1995), each of the four derived scale scores was entered for both husband and wife. Inspection of the cluster analyses revealed that a five‐cluster solution provided a feasible outcome.…”
Section: Resultsmentioning
confidence: 99%
“…This strategy has been used in other studies employing similar clustering techniques (see Fowers & Olson, 1992; Lavee & Olson, 1993). Following a procedure outlined by Bayer and Day (1995), each of the four derived scale scores was entered for both husband and wife. Inspection of the cluster analyses revealed that a five‐cluster solution provided a feasible outcome.…”
Section: Resultsmentioning
confidence: 99%
“…Intergenerational intimacy, autonomy versus fusion, intergenerational intimidation, and intergenerational individuation significantly predicted various identity statuses. The few studies that have examined intergenerational transmission of patterns of relating among married couples have found some support for assumptions of intergenerational influence (Bayer & Day, 1995;Sabatelli & Bartle-Haring, 2003;Winn, Crawford, & Wampler, 1995). For example, Sabetelli and Bartle-Haring (2003) found that husbands and wives' familyof-origin experiences significantly predicted marital adjustment among husbands and wives.…”
Section: Intergenerational Perspectives In Family Therapymentioning
confidence: 99%
“…Les scores aux PAFS-Q sont associés à la qualité de la satisfaction conjugale (Bray et ai., 1984b;Côté, 1993), au degré de flexibilité dans les échanges conjugaux (Winn, Crawford, & Wampler, 1995), à l'intensité de la codépendance chez les couples dont un membre est alcoolique (Prest, Benson, & Protinsky, 1998) et à la qualité de résolution des stades de la vie adulte tels que définis par Erikson (Cebik, 1988), dont entre autres la question de l'intimité (Garbarino et al, 1995). De plus, le PAFS-Q permet de créer une typologie conjugale (quatre types) (Bayer, 1995). Outre ces associations significatives à diverses composantes de la vie conjugale, la qualité des liens intergénérationnels tels que mesurés par le PAFS-Q est significativement associée à la qualité du développement général du jeune adulte (Johnson & McNeil, 1998;Johnson & Nelson, 1998) mais aussi de l'adulte plus mature (Cebik, 1988;JRabin, Bressler, &J?rager, 1993).…”
Section: Hypothèses De Rechercheunclassified